Superior interfacial toughening of hybrid metal-composite structural joints using 3D printed pins. (May 2023) - Bagnato, Tiana; Ravindran, Anil R.; Mirabedini, Azadeh; Ladani, Raj B.; Kandare, Everson; Orifici, Adrian C.; Chang, Paul; Wang, John; Mouritz, Adrian P.
Abstract: An experimental investigation is presented into the enhancement of interfacial toughness properties of hybrid titanium-to-composite structural joints using 3D printed metal pins created using selective laser melting (SLM). The joints were formed by printing an orthogonal array of thin (1.0 mm) diameter titanium pins over the titanium substrate using SLM, which were then embedded into a carbon-epoxy composite substrate to create a high toughness interface. SLM Ti-pinned hybrid joints were evaluated for the first time with and without film adhesive, which is co-bonded between the titanium and composite substrates. The SLM Ti-pins increased the modes I and II interfacial toughness of the hybrid joints by up to about 19- and 11-fold, respectively. The study reveals that pins created using SLM are highly effective at the strengthening and toughening of hybrid metal-composite joints, with the need for adhesive bonding dependent on the loading condition.